Blocking P2X7 receptor with AZ 10606120 exacerbates vascular hyperpermeability and inflammation in murine polymicrobial sepsis. Issue 11 (6th June 2022) - Meegan, Jamie E.; Komalavilas, Padmini; Cheung‐Flynn, Joyce; Yim, Tsz Wing; Putz, Nathan D.; Jesse, Jordan J.; Smith, Kyle D.; Sidorova, Tatiana N.; Lee, Han Noo Ri; Tomasek, Toria; Shaver, Ciara M.; Ware, Lorraine B.; et al.
Abstract: Sepsis is a devastating disease with high morbidity and mortality and no specific treatments. The pathophysiology of sepsis involves a hyperinflammatory response and release of damage‐associated molecular patterns (DAMPs), including adenosine triphosphate (ATP), from activated and dying cells. Purinergic receptors activated by ATP have gained attention for their roles in sepsis, which can be pro‐ or anti‐inflammatory depending on the context. Current data regarding the role of ATP‐specific purinergic receptor P2X7 (P2X7R) in vascular function and inflammation during sepsis are conflicting, and its role on the endothelium has not been well characterized. In this study, we hypothesized that the P2X7R antagonist AZ 10606120 (AZ106) would prevent endothelial dysfunction during sepsis. As proof of concept, we first demonstrated the ability of AZ106 (10 µM) to prevent endothelial dysfunction in intact rat aorta in response to IL‐1β, an inflammatory mediator upregulated during sepsis. Likewise, blocking P2X7R with AZ106 (10 µg/g) reduced the impairment of endothelial‐dependent relaxation in mice subjected to intraperitoneal injection of cecal slurry (CS), a model of polymicrobial sepsis. However, contrary to our hypothesis, AZ106 did not improve microvascular permeability or injury, lung apoptosis, or illness severity in mice subjected to CS. Instead, AZ106 elevated spleen bacterial burden and circulating inflammatory markers. In conclusion, antagonism of P2X7R signaling during sepsis appears to disrupt the balance between its roles in inflammatory, antimicrobial, and vascular function. Abstract : In this study, blocking the P2X7R with the specific and highly selective antagonist AZ 10606120 completely restored vascular dysfunction in rat aorta in response to IL‐1β and partially restored vascular dysfunction in a murine model of polymicrobial sepsis induced by intraperitoneal injection of cecal slurry. However, AZ106 did not confer protective benefits regarding vascular hyperpermeability or injury, lung apoptosis, circulating inflammatory markers, illness severity, or bacterial burden. Conversely, AZ106 treatment in the CS model resulted in increased spleen bacterial burden and circulating inflammatory markers.